AMERICAN VALUES PORTRAYED ON JAMES J. BRADDOCK AS THE MAIN CHARACTER OF CINDERELLA MAN MOVIE - VIARENI, EVRI YUSMAF (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: American values, Cinderella Man movie The history of American values cannot be separated from the history of America. American values are the representation of the main reason why many immigrants come to this Uncle Sam country. They believe that they can achieve their dream in America. They think that in America everyone can pursue their dream because in this land all men are created equal. Like one of the embodiment of human rights stated in the Declaration of Independence “all men are created equal” is the famous notion for all Americans to be successful and have a better life. There are six basic of American values, three represent reasons why immigrants were drawn to America: the chance for individual, equality of opportunity and material wealth. In order to achieve this benefit, however there were prices to be paid: self-reliance, competition and hard work.In this thesis, the writer will also use historical background to support andremind again the occurrences and effects of great depression era, because the setting of the movie took on that era.The finding shows that the main character of Cinderella Man movie, James J.Braddock represents American values. The writer suggest for the next researcher to analyse this movie using Marxist theory about the class system in America. The next researcher can use this theory to reveal the economy class changing in the main character of the movie, James J. Braddock. Besides, the next researcher can also by seeing it from the relationship between bourgeoisie and proletariat.